Vibrational Spectral Studies of 1,4-Dihydroxy-2,3,5-trimethylbenzene. - ILANGO, G.; BALACHANDRAN, V.; ARIVAZHAGAN, M.; JOHN XAVIER, R. (Asian Journal of Chemistry, 2010)
Vibrational spectral studies of 1,4-dihydroxy-2,3,5-trimethylbenzene has been carried out by assuming CS point group symmetry. The FT-IR and FT-Raman spectra are interpreted on the basis of force field calculations and potential energy distributions.